Utilization of Snails as Liquid Organic Fertilizer (POC) with the Anaerobic Composter Tube Method - Syahrani Pramia Lestari; Dwi Rossani Nur Afifah; Lukhi Mulia Shitophyta; Aster Rahayu (Universitas Ahmad Dahlan, 2025)
Indonesia is a country with thousands of islands inhabited by flora and fauna, with these conditions, many organisms such as snails are found. Snails are often considered pests by vegetable farmers. Snails contain amino acids, nitrogen, phosphorus, potassium, and protein that can help increase plant growth and development. The purpose of this study was to utilize snails as liquid organic fertilizer, to find out the process of making liquid organic fertilizer from snails, to find out the differences in the content of liquid organic fertilizer from the three samples, to find out the comparison of growth in eggplant as a test medium, and to find out the effect of the comparison of molasses and snails. The research methods include preparation of raw materials, boiling and crushing snails, mixing materials, and the fermentation process. After that, the fertilizer from the study was analyzed to determine the content of N, P, K. The results showed that for the analysis of NPK content obtained in a sample of 100 grams of snails, the N content value was 0.028%, P 2 O 5 0.016%, K 2 O 0.003%. In a sample of 300 grams of snails, the N content value is 0.041%, P 2 O 5 0.043%, K 2 O 0.050%. Comparative analysis of purple eggplant plants given snail POC and not given snail POC can be seen the difference in stem height and leaf width. In sample 1 which was not given snail POC, the stem height was 9 cm and the leaf width was 5.4 cm, sample 2 with 100 grams of snails had a stem height of 11.2 cm and a leaf width of 7.1 cm, in sample 3 with 300 grams of snails had a stem height of 12.3 cm and a leaf width of 7.7 cm, while in sample 4 with 500 grams of snails which had a stem height of 15.4 cm and a leaf width of 9.5 cm. This shows that sample 4 with 500 grams of snails has a very good growth rate. The differences in the research test results are due to differences in the dosage or variation and weight of snails and molasses given to each sample.